UTILIZATION OF A PICO HYDRO POWER PLANT AT AL-IKHLAS ISLAMIC BOARDING SCHOOL IN MALANG REGENCY - Hidayat, Mohammad Noor; Ronilaya, Ferdian; Heryanto Eryk, Irwan; Wibowo, Sapto; Asrori, Asrori; Saputra, Masramdhani (LPPM Univ. Ibn Khaldun Bogor, 2023)
Al-Ikhlas Yatim Dhuafa Islamic Boarding School is ± 12.6 km from Malang City. If you look at it geographically, the location of this community service program is located at coordinates 7°58'27.0